2013
DOI: 10.1186/1479-5876-11-40
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of left ventricular remodeling after myocardial infarction with eight weeks L-thyroxine treatment in rats

Abstract: BackgroundLeft ventricular (LV) remodeling following large transmural myocardial infarction (MI) remains a pivotal clinical issue despite the advance of medical treatment over the past few decades. Identification of new medications to improve the remodeling process and prevent progression to heart failure after MI is critical. Thyroid hormones (THs) have been shown to improve LV function and remodeling in animals post-MI and in the human setting. However, changes in underlying cellular remodeling resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 46 publications
8
53
0
Order By: Relevance
“…After myocyte injuries, the infarct size increases and causes wall thinning and ventricular dilatation [22,23]. Our results also showed that apelin-13 given 24 h after MI for five days could improve myocardial structure and remodelling parameters, as shown in Figure 1.…”
Section: Discussionsupporting
confidence: 60%
“…After myocyte injuries, the infarct size increases and causes wall thinning and ventricular dilatation [22,23]. Our results also showed that apelin-13 given 24 h after MI for five days could improve myocardial structure and remodelling parameters, as shown in Figure 1.…”
Section: Discussionsupporting
confidence: 60%
“…But, over time the spared segment lengthens. Lengthening with minimal change in wall thickness of the spared segment is clearly due to an increase in myocyte length only with no change in CSA (2,7,21). Remodeling of myocyte shape is consistent with anatomical findings.…”
Section: Cardiac Remodeling: Is It Real? Does It Make Sense?supporting
confidence: 74%
“…Consequently, there is a possibility that exogenous T 4 may be inadequately converted to active T 3 in the heart and may also inhibit T 3 secretion from the thyroid gland. Nonetheless, it should be pointed out that we have also observed rather dramatic improvements with T 4 treatment of rat models of HF (2,22).…”
Section: Discussionmentioning
confidence: 92%
“…All images were captured using an Olympus BX53 and cellSens imaging software (Olympus, Tokyo, Japan). Myocardial fibrosis was examined morphometrically using Masson's trichrome staining as described previously (2).…”
Section: Methodsmentioning
confidence: 99%